Postural and Balance Disorders in Patients with Parkinson’s Disease: A Prospective Open-Label Feasibility Study with Two Months of Action Observation Treatment - Andrea Santamato; Maurizio Ranieri; Nicoletta Cinone; Lucia Anna Stuppiello; Giovanni Valeno; Jula Laura De Sanctis; Francesca Fortunato; Vincenzo Solfrizzi; Antonio Greco; Davide Seripa; Francesco Panza (Parkinson's Disease)
Action observation treatment has been proposed as therapeutic option in rehabilitation of patients affected by Parkinson’s disease (PD) to improve freezing of gait episodes. The purpose of this prospective open-label feasibility study was to evaluate the impact of 8-week action observation training (video-therapy) for the treatment of postural instability and balance impairment in PD patients. Fifteen PD patients aged under 80 years with scores of 1 to 3 on the Hoehn and Yahr staging and without evidence of freezing of gait were recruited. They underwent 24 sessions of video-therapy training based on carefully watching video clips on motor tasks linked to balance, subsequently performing the same observed movements. No statistically significant differences were observed in the identified outcome measures with the Berg Balance Scale and the Activities-Specific Balance Confidence Scale after two months of follow-up. In the present study, a short course of action observation treatment seems to be not effective in reducing balance impairments and postural instability in patients affected by mild to moderate PD. Further studies with larger samples, longer follow-up period, and standardized protocols of action observation treatment are needed to investigate the effects of this rehabilitation technique in the management of postural and balance disorders of PD patients.